2020
DOI: 10.3390/plasma3020005
|View full text |Cite
|
Sign up to set email alerts
|

Spatially-Resolved Spectroscopic Diagnostics of a Miniature RF Atmospheric Pressure Plasma Jet in Argon Open to Ambient Air

Abstract: The spatially-resolved electron temperature, rotational temperature, and number density of the two metastable Ar 1 s levels were investigated in a miniature RF Ar glow discharge jet at atmospheric pressure. The 1 s level population densities were determined from optical absorption spectroscopy (OAS) measurements assuming a Voigt profile for the plasma emission and a Gaussian profile for the lamp emission. As for the electron temperature, it was deduced from the comparison of the measured Ar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
(58 reference statements)
1
3
0
Order By: Relevance
“…A typical measurement along with the corresponding Voigt fit is presented in figure 2. Based on detailed line broadening analysis, the experimental conditions investigated herein lead to a T g value in the order of 2200 ± 200 K. This value agrees well with those reported by Durocher-Jean et al [42] for microwave plasma jets; however, it is considerably higher than the values commonly observed for low and mid-frequency plasma jets (T g ∼ 300-550 K [50,51]). Considering that the population of the Ar 1s state is sufficiently small within the range of experimental conditions employed herein (typically below 10 9 cm −3 [42]), the radiation trapping of Ar 2p-to-1s transitions was neglected [41].…”
Section: Experimental Setup and Diagnosticssupporting
confidence: 91%
“…A typical measurement along with the corresponding Voigt fit is presented in figure 2. Based on detailed line broadening analysis, the experimental conditions investigated herein lead to a T g value in the order of 2200 ± 200 K. This value agrees well with those reported by Durocher-Jean et al [42] for microwave plasma jets; however, it is considerably higher than the values commonly observed for low and mid-frequency plasma jets (T g ∼ 300-550 K [50,51]). Considering that the population of the Ar 1s state is sufficiently small within the range of experimental conditions employed herein (typically below 10 9 cm −3 [42]), the radiation trapping of Ar 2p-to-1s transitions was neglected [41].…”
Section: Experimental Setup and Diagnosticssupporting
confidence: 91%
“…For example, a judicious control of neutral gas heating in non-thermal plasmas at atmospheric pressure plays a critical role in plasma processing of heat-sensitive materials like polymers and human tissue [3][4][5], in fuel synthesis through plasma dissociation of complex molecules [6][7][8][9], and in plasma deposition of functional, nanostructured coatings [10][11][12]. Regrettably, acquiring T g while Sainct et al reported a decrease of T g from 400 K to 380 K along the outlet of an RF atmospheric-pressure argon plasma jet sustained with 40 W [15]. Rayleigh scattering is a well-established way of acquiring T g , relying on photons scattering on electrons bound to atoms or molecules [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not so easy to capture the effluent image if T gas is close to the room temperature (T room ). The employment of thermocouples for T gas measurements are also reported on the literature [33][34][35]. Nonetheless, this kind of device usually has metallic components in the sensor probe.…”
Section: Introductionmentioning
confidence: 93%